"See it, Address it, Solve it” framework to support understanding and facilitate development of adaptive expertise in training and practice (Canadian Medical Education Journal, 2026)
Background: Adaptive expertise is crucial in generalist areas of medicine, where practitioners must navigate both routine and novel clinical situations daily. While adaptive expertise has been well described in the literature, there is a gap when it comes to concrete guidance for teaching and assessing adaptive expertise. This study aims to develop an evidence-guided model to support clinical educators and learners with understanding adaptive expertise so that it can be taught and assessed in the context of clinical training.Methods: The research team used a three-stage process to develop a model of adaptive expertise. In Stage 1, a panel of experts created a concept map to describe elements of adaptive expertise in the context of the generalist clinical workplace, followed by a scoping review of the adaptive expertise literature in Stage 2. In Stage 3, the panel integrated the original concept map with the results of the scoping review to create a model of adaptive expertise in the context of the generalist clinical workplace using consensus development panel methodology.Results: The “See it, Address it, Solve it” model illustrates how generalist practitioners move through three iterative phases: identifying gaps in knowledge or care (“See it”), engaging in innovative and context-specific problem-solving (“Address it”), and implementing and refining solutions using clinical judgement (“Solve it”).Conclusions: The “See it, Address it, Solve it” model offers a practical resource to support both understanding of adaptive expertise in the clinical workplace, and help educators identify elements of adaptive expertise to facilitate teaching and assessment.